Study on the Correlation Between Smoking, Drinking and Students' Academic Performance - Liu, Zhengyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
The habits of students, with a focus on smoking and alcohol consumption, about their academic performance, is an essential area of study. The findings of this study will seek to fill a significant gap in recent empirical evidence concerning the issue at hand. For the research, data from student questionnaires and academic records were used, while correlation and regression analyses were done to test these relationships. The findings show that high smoking and drinking frequency is significantly associated with poor academic achievement. Hence, the finding underlines a call for specific interventions in promoting the health and educational outcomes of students. The updated empirical evidence in this study will be instrumental in updating the formulation of policies and interventions that might reduce the negative impacts of smoking and alcohol use on the academic achievements of students. The updated empirical evidence provided by this study will be instrumental in formulating policies and interventions aimed at reducing the negative impacts of smoking and alcohol use on students' academic achievements. Based on the results, it is concluded that reducing smoking and alcohol consumption among students can lead to better academic performance, highlighting the critical need for health promotion programs within educational institutions.